2019
DOI: 10.18551/rjoas.2019-09.13
|View full text |Cite
|
Sign up to set email alerts
|

Structural Capital Mediates Human Capital Effect Based on Asta Brata Against Financial Performance of People's Rural Banks in Bali

Abstract: The purpose of this study is to examine and explain the effect of human capital and structural capital on the financial performance of Rural Credit Banks in Bali, both in direct and indirect relationships. This study uses a mixed research design, a research method that combines quantitative and qualitative research designs. The population in this study is conventional BPRs in the Province of Bali, totaling 136 BPRs (Bank Indonesia, 2016), with a sample of 60 BPRs in Bali. The unit of analysis is 60 BPR leaders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…A study on people´s rural banks in Bali, Indonesia, by Ayu et al (2019), found out that while human capital did not have a significant effect on the financial performance of those banks when mediated by structural capital, its influence on the financial performance of the banks increased.…”
Section: Introductionmentioning
confidence: 99%
“…A study on people´s rural banks in Bali, Indonesia, by Ayu et al (2019), found out that while human capital did not have a significant effect on the financial performance of those banks when mediated by structural capital, its influence on the financial performance of the banks increased.…”
Section: Introductionmentioning
confidence: 99%
“…BPR is limited by various requirements, so it cannot act freely for commercial banks. The limitations of BPR activities are also associated with the mission of establishing BPR itself (Ayu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%